2016
DOI: 10.1111/jerd.12233
|View full text |Cite
|
Sign up to set email alerts
|

Can Reduced‐Step Polishers Be as Effective as Multiple‐Step Polishers in Enhancing Surface Smoothness?

Abstract: Reduced-step systems used after a prepolisher can be an acceptable alternative to multiple-step systems on enhancing the surface smoothness of a nanohybrid composite; however, their effectiveness depends on the materials' properties. (J Esthet Restor Dent 29:31-40, 2017).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
2
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 19 publications
4
39
2
8
Order By: Relevance
“…The flexible form can adapt to nearly every surface of a restoration, minimizing heat formation and unwanted pressure during polishing. Several studies concluded that flexible aluminum discs are the best instruments for producing the surface glossiness [8,33]. However, one could also recommend the abrasive polishing points, since points may be used clinically in areas that are not readily accessible to other polishing systems.…”
Section: Discussionmentioning
confidence: 99%
“…The flexible form can adapt to nearly every surface of a restoration, minimizing heat formation and unwanted pressure during polishing. Several studies concluded that flexible aluminum discs are the best instruments for producing the surface glossiness [8,33]. However, one could also recommend the abrasive polishing points, since points may be used clinically in areas that are not readily accessible to other polishing systems.…”
Section: Discussionmentioning
confidence: 99%
“…Finishing procedures are performed to remove surface defects and small excesses around restorations in order to achieve adequate final anatomy (Kemaloglu, Karacolak, & Turkun, ), while polishing reduces surface roughness and fine scratches originated from finishing, so a surface as smooth and glossy as natural enamel can be achieved (Terry & Geller, ). For finishing and polishing systems to be effective, the hardness of the abrasive/cutting material must be higher than that of the restorative material (Turssi, De Moraes Purquerio, & Serra, ).…”
Section: Introductionmentioning
confidence: 99%
“…Os sistemas de acabamento e polimento disponíveis geralmente possuem uma ampla variedade de discos, escovas e borrachas 10 . Alguns sistemas foram inseridos no mercado com a intenção de reduzir a quantidade de passos e simplificar a etapa de acabamento e polimento, entretanto os resultados obtidos por esses materiais ainda são controvérsios 8,12 .…”
Section: Introductionunclassified
“…No presente estudo, o uso da tira de poliéster teve resultado semelhante aos demais protocolos de polimento. O protocolo mais eficiente para a redução da rugosidade foi o que envolveu discos abrasivos, broca multi-laminada e espirais, porém, foram estatisticamente semelhantes aos demais.Determinar os materiais e técnicas mais apropriados para acabamento e polimento, que alcançam um bom resultado de brilho e lisura superficial com menor quantidade de passos é um fator importante12,20 . O uso de um protocolo com passos reduzidos, tal como, espirais com irrigação, se mostra tão efetivo quanto protocolos com maior quantidade de passos.…”
unclassified
See 1 more Smart Citation